The Buddha's Tooth: Western Tales of a Sri Lankan Relic By J. S. Strong (2021) - Angowski, Elizabeth (Body and religion, 2023)
The Buddha's Tooth: Western Tales of a Sri Lankan Relic By J. S. Strong (2021) Chicago: University of Chicago Press, 352pp.